УДК 1082 SYSTEMATIC ANALYSIS OF THE STATE OF CONTROL OF THE TECHNOLOGICAL PROCESSES OF UNDERGROUND LEACHING - Ismanova, Klara (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
Оbjective: to create optimal algorithms and programs that calculate the main geo-technological indicators of the mineral mixing process, to distinguish the factors affecting the management process in mine processing. Methods: Fourier, Laplace, Bubnov-Galyorkin’s substitution and finite-difference methods of approximation are used to solve the diffusion problem of the underground leaching (UL) process. Results: One of the geo-technological methods used in the extraction of minerals, the method of mineral mixing, was systematically analyzed and the process of extracting useful components using this method was studied. Two-dimensional mathematical control models that are suitable for this process were developed. As a result of solving these models, the dynamics of concentration changes and the values of parameters affecting the effective course of the process were analyzed using various diagrams. Conclusions: in order to calculate the decision-making parameters when conducting a computational experiment and process control, underground leaching and their mathematical models must be compatible with natural processes and the parameters involved in it, and software tools must also be developed to visualize the calculation results corresponding to the mathematical model.